Cuentos colombianos - García Mejía, Hernando; Carrasquilla, Tomás; Gómez, Efe; Corral, Jesús del; Fuenmayor, José Félix; Arias Suárez, Eduardo ‎; López Gómez, Adel; Téllez, Hernando; Cardona Jaramillo, Antonio (Colección los mejores)
Una visión crítica y desapasionada de la gran literatura de hoy y siempre